Rural Space Modeling - Kurowska, Krystyna; Kowalczyk, Cezary (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Rural areas have a very important role in society and the economy. They provide residence and employment and also serve as recreational sites, enabling visitors to enjoy unspoiled nature. Rural areas not only supply raw materials and products, but they also provide space for other functions. Spatial planning has a very important role in the process of rural space modeling. It is also important to study local and external conditions. A rural development framework can be proposed based on an evaluation of the observed phenomena. The following list provides some examples of topics of interest to ensure the consistency of the papers in this Special Issue: - Spatial planning;- Spatial order;- Institutional efficiency;- Spatial, financial, and environmental effects of planning studies;- The urbanization of rural areas;- Town-village relationships;- Social, cultural, economic, environmental, and spatial aspects of rural development. Dynamically growing new technologies (e.g., multi-criteria methods and GIS tools) are gaining popularity worldwide as tools for use in spatial analysis. This Special Issue focuses on the practice and theory of the application of modern technologies in rural space modeling and rural area development planning.The monograph includes papers on contemporary research directions on rural space modeling in areas such as spatial planning, spatial order, spatial-temporal analysis, land use change, environmental aspects, etc. The integration of different data, GIS tools and modeling can provide valuable support for rural space modeling and decision making.